Encyklika Laudato si’ papieża Franciszka. Kontynuacja tradycji Kościoła czy próba nowego spojrzenia? - Zarębska, Małgorzata (Studia Politicae Universitatis Silesiensis, 2018)
Abstract: The Pope Francis’s encyclical Laudato si’ Continuation of the Church’s teaching or an attempt at a new perspective? The encyclical Laudatio si’ is the first social encyclical letter by Pope Francis. Its key reference point is the apostolic exhortation Evangelii Gaudium promulgated in 2013. In the latter, the pope presents four „principles”: 1. „Time is greater than space”; 2. „Unity prevails over conflict”; 3. „Realities are more important than ideas”; 4. „The whole is greater than the part.” The encyclical Laudatio si’ in its entirety is devoted to ecology. However, by ecology the pope means the „integral ecology.” And this is where the previously mentioned principles apply. Following the footsteps of St. Francis, the contents of the encyclical offers new perspectives to the teaching and praxis of the Catholic Church. Key words: encyclical, ecology, integral ecology, Catholic Church